Hypothyroidism in Female Athletes: Differentiation from Overtraining Syndrome and Implications for Athletic Performance – A Narrative Review - Struzynska, Ewelina; Ziółkowska, Weronika; Wisoky, Wiktor; Czapla, Natalia; Łopińska, Joanna; Ignyś, Piotr; Graczyk , Natalia; Graczyk, Martyna; Majchrzycka, Marta; Majchrzak, Mateusz (Quality in Sport, 2026)
Introduction. Hypothyroidism and overtraining syndrome (OTS) may present with similar symptoms in female athletes, including fatigue, reduced exercise tolerance, mood disturbances, sleep problems, and impaired performance, which may complicate differential diagnosis. Aim of the study. To review the overlap between hypothyroidism and OTS in female athletes, identify key elements of differential diagnosis and discuss implications for treatment and return to sport. Material and Methods. A narrative literature review was conducted using PubMed, Scopus, and Google Scholar for studies published between 1990 and 2025, with emphasis on review articles, consensus statements, clinical guidelines, and papers addressing symptom overlap, laboratory evaluation, and athletic performance. Results. Both hypothyroidism and OTS are associated with persistent fatigue, delayed recovery, sleep disturbances, mood changes, and reduced training capacity. However, hypothyroidism is more often linked to cold intolerance, weight gain, cognitive complaints, and other features of endocrine dysfunction. Thyroid-stimulating hormone (TSH) and free thyroxine (fT4) are the most useful laboratory markers in differential diagnosis, whereas biochemical abnormalities in OTS remain nonspecific. Coexisting low energy availability and relative energy deficiency in sport (RED-S) may further complicate clinical assessment. Conclusions. In female athletes with fatigue and declining performance, hypothyroidism should be considered alongside OTS, especially when symptoms persist despite training modification. Early recognition of thyroid dysfunction may support appropriate treatment and safer return-to-sport decisions.